What are the barriers affecting the use of earth as a modern construction material in the context of circular economy?. (January 2019) - Morel, JC; Charef, R
Abstract: One path to decrease the impacts of construction is to switch from the current take-make-dispose extractive industrial model, to a circular economy scheme. Building with prime materials and especially with earth (locally available soils containing clay), is a way to foster the circularity of the materials because the unstabilised earth is 100% infinitely reusable. Earth architecture involves different modern and ancient techniques of construction like rammed earth or compressed earth block masonry. However, the development of new earth building is still limited to a niche in spite of its high circularity potential in a modern context. We have performed a review of the barriers that may affect the uptake of the earth as a building material. We have studied journal papers and some findings are based on the experience of the authors as practitioners and researchers. The identified barriers can be classified in Steering mechanisms, Process, Economics, Client understanding and Underpinning knowledge. We have discussed the barriers and reviewed some possible paths to smooth the existing obstacles to the development of earth architecture.